Reserve Requirements, the Maturity Structure of Debt, and Bank Runs - Al-Zein, Eza Ghassan (IMF Working Papers; Working Paper ;, 2008)
The paper looks at the relationship between reserve requirements and the choice of the maturity structure of external debt in a general equilibrium setup, by incorporating the role of international lenders. A date- and maturity-specific reserve requirement is a fraction of the debt to be deposited in a non-interest bearing account at the central bank. At maturity, the central bank returns the reserves. There exist some specific combinations of date- and maturity-specific reserve requirements that reduce the vulnerability to bank runs. In such setup, lenders may still want to provide new short-term lending to the bank after a bank run.